Condition evaluation model of fluid power system in gradual failure based on data envelopment analysis. (30th March 2015) - Zhao, Xiuxu; Zhou, Chuanli; Zhao, Lei; Zhang, Shuanshuan; Wen, Pengfei; Jiang, Jihai
Highlights: A condition evaluation model is proposed to analyze fluid power system in gradual failure. The input and output index for fluid power system condition evaluation is determined. The relative efficiency of fluid power system in gradual failure can be calculated. Leakage was selected as an application example to verify this model. Experimental results show the model based on DEA can reveal the leakage degree. Abstract: In the condition based maintenance, quantitative evaluation of the system in gradual failure is important foundation for timely and reasonable decision making. However, there are several types of components in fluid power system, and they have complex mutual constraints between different component's performance parameters, this make it difficult to evaluate the condition of fluid power system in gradual failure. To solve this problem, the paper proposes a model based on data envelopment analysis (DEA) to analyze the efficiency change degree of fluid power system. Leakage of fluid power system is selected as an application example and the sample data are collected through a leakage experiment system, and the experiments were carried out in single component failure mode and multi-components failure mode respectively. The main contents of this research include determining the input and output index of fluid power system for condition evaluation, modeling based on DEA and calculating the relative efficiency of fluid power system in gradual failure. Experimental results show that condition evaluation model based on DEA can reveal the leakage degree in fluid power system, and provide a feasible solution for accurate assessment of fluid power system in gradual failure.